Mulberry cellulose fiber and preparation method thereof
Through microwave treatment, acid bath pretreatment, microbial fermentation treatment, enzyme degumming and cooking, mulberry cellulose fibers are modified, which solves the problems of low degumming efficiency, large structural damage and serious pollution in the existing technology, and achieves the goal of achieving The fiber length uniformity, fineness consistency, surface smoothness and mechanical properties are improved.
Patent Information
- Application Number
- CN202411280472.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing degumming method of mulberry cellulose fiber has problems such as time-consuming, low efficiency, large structural damage, serious pollution, high cost, unstable enzyme activity, poor fiber stability, and incomplete degumming, which limits its application in the textile field. .
Using a comprehensive method of microwave treatment, acid bath pretreatment, microbial fermentation treatment, enzyme degumming treatment and cooking, mulberry cellulose fiber is modified, and the adhesion between pectin and cellulose is reduced through microwave treatment, and the acid bath is removed. Part of pectin and impurities, microbial fermentation destroys the macromolecular structure of pectin, enzyme degumming treatment completely removes non-cellulose substances, cooking further improves the stability of the fiber, and forms a cross through the modification steps of permeate and phosphate buffer. Connected structure to enhance the mechanical properties of fibers.
The length uniformity, fineness consistency, surface smoothness and mechanical properties of mulberry cellulose fibers have been achieved, which reduces the strength unevenness and surface hairiness, and improves the overall performance and application range of the fibers.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fibers, and in particular relates to mulberry cellulose fiber and a preparation method thereof. Background Art
[0002] my country has abundant mulberry resources, with a mulberry area of 5.33×105hm2. 2 , only a small part of the discarded mulberry branches is used in the pharmaceutical industry every year, and most of them are incinerated, causing air pollution. In order to turn waste into treasure and make better use of natural plant resources, mulberry bark cellulose fiber prepared from mulberry bark as raw material has attracted widespread attention. The cellulose content in mulberry bark is low, and the content of hemicellulose, lignin and pectin is high. The main component of mulberry bark cellulose fiber is cellulose, so the degree of degumming is directly related to the spinnability and dyeability of mulberry bark cellulose fiber. At present, the commonly used degumming methods mainly include natural degumming method, chemical degumming method, enzyme degumming method, etc. The natural degumming method is time-consuming and inefficient, and the chemical degumming method causes greater damage to the fiber structure and also causes certain pollution to the environment. The enzyme degumming method is pollution-free, but there are problems such as high cost, unstable enzyme activity, poor fiber stability, and incomplete degumming.
[0003] Mulberry cellulose fiber has unique properties. Compared with cotton fiber, it has higher strength, better warmth retention and better wear resistance. In addition, mulberry cellulose fiber also contains antibacterial ingredients such as tannic acid, flavonoids and phenolic compounds, which makes its antibacterial effect better. After degumming, the antibacterial effect can reach more than 60%. The price of mulberry cellulose fiber is much lower than that of cotton fiber, but mulberry cellulose fiber is shorter, has a high rate of short fibers, and has a high rate of uneven strength. It is more difficult to spin it purely, and there is more hairiness on the surface after the yarn is formed. Therefore, mulberry cellulose fiber is usually blended with cotton fiber to improve the quality of the yarn.
[0004] The mulberry cellulose fiber obtained after degumming is an irregular columnar object with an irregular or elliptical cross section, no central cavity structure, a rough and uneven surface, and holes or gaps. The diameter uniformity is poor, so the fiber strength unevenness rate is high. Compared with cotton fiber, mulberry cellulose fiber is short and hard, not easy to deform after being stressed, poor cohesion between fibers during winding, low yarn strength, insufficient yarn softness, and high process difficulty, which limits its application in the textile field. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a mulberry cellulose fiber and a preparation method thereof, so as to achieve the invention purpose of modifying the mulberry cellulose fiber to improve the overall performance of the fiber and reduce the difficulty of its blending.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A mulberry cellulose fiber and a preparation method thereof, the preparation method comprising the following steps:
[0008] S1. Microwave treatment
[0009] Soak the mulberry bark in water and microwave it, then dry it in the sun for 24 hours after cooling, and then beat it to remove impurities.
[0010] Preferably, the microwave treatment has a power of 600 to 1000 W and a time of 20 to 30 min.
[0011] Microwave treatment can accelerate the entry of water molecules into the mulberry bark, reduce the adhesion between pectin and cellulose, and lay the foundation for subsequent degumming.
[0012] S2. Preprocessing
[0013] The mulberry bark obtained by microwave treatment is immersed in an acid bath for 60 to 80 minutes and then washed with water.
[0014] Preferably, the acid bath comprises citric acid, wherein the concentration of the citric acid is 1.5-3 g / L; the temperature of the acid bath is 50-60° C., and the bath ratio is 1:18-20.
[0015] Pretreatment can remove part of the pectin and impurities in the mulberry bark by using a milder weak acid and controlling the temperature at 50-60°C to avoid hydrolysis of cellulose in the mulberry bark.
[0016] S3. Microbial fermentation treatment
[0017] The mulberry bark obtained by pretreatment is added into the composite bacterial liquid for fermentation treatment, and then washed with water after the treatment.
[0018] Preferably, the mass fraction of the composite bacterial liquid is 20-24%; the composite bacterial liquid contains EM bacteria, Bacillus licheniformis and Bacillus subtilis, and the mass ratio of the EM bacteria, Bacillus licheniformis and Bacillus subtilis is 4-6:10-12:2-4; the EM bacteria, Bacillus licheniformis and Bacillus subtilis are all purchased from Shandong Xinzhuoyuan Chemical Co., Ltd.
[0019] Preferably, the fermentation temperature is 30-35° C. and the fermentation time is 2-3 days.
[0020] After microbial fermentation, the macromolecular structure of pectin in mulberry bark is destroyed and the structure between molecules becomes loose, which is conducive to subsequent enzymatic degumming.
[0021] S4. Enzyme degumming treatment
[0022] The mulberry bark treated with microbial fermentation is added into an active enzyme solution for enzymatic degumming treatment.
[0023] Preferably, the concentration of laccase in the active enzyme solution is 0.4-0.6 g / L, and the concentration of pectinase is 1-1.5 g / L; the temperature of the enzyme degumming treatment is 45-50° C., the time is 6-8 h, and the bath ratio is 1:28-30.
[0024] Preferably, the enzyme activity of the laccase is 10000U, and the enzyme activity of the pectinase is 8600U.
[0025] S5, Cooking
[0026] The mulberry bark treated with enzyme degumming is added into alkali solution for scouring, and then washed with water after scouring.
[0027] Preferably, the concentration of sodium hydroxide in the alkali solution is 12-16 g / L, the concentration of sodium tripolyphosphate is 5-8 g / L, and the concentration of sodium silicate is 7-10 g / L.
[0028] After enzyme degumming treatment, mulberry bark still contains residual pectin, hemicellulose and lignin. Scouring can further reduce the content of non-cellulose substances in mulberry bark and improve the stability of the fiber.
[0029] S6. Modification
[0030] The mulberry bark after being boiled and washed is first added into the permeate and soaked for 40 to 60 minutes, with a bath ratio of 1:10 to 12; then added into the phosphate buffer solution, heated to 30 to 35°C and reacted for 2 to 4 hours to obtain the modified mulberry bark.
[0031] Preferably, the preparation method of the permeate is: add four-arm polyethylene glycol-maleimide, four-arm polyethylene glycol-N-hydroxysuccinimide ester, and sodium dioctyl sulfosuccinate to deionized water and stir for 5 to 10 minutes to obtain the permeate.
[0032] Preferably, by weight, the permeate contains 10 to 14 parts of four-arm polyethylene glycol-maleimide, 13 to 16 parts of four-arm polyethylene glycol-N-hydroxysuccinimide ester, 1 to 3 parts of sodium dioctyl sulfosuccinate, and 85 to 95 parts of deionized water.
[0033] Preferably, the pH of the phosphate buffer is 7.7-8.5.
[0034] The structure of mulberry bark after degumming is relatively loose, with holes and gaps on the surface. Under the action of sodium dioctyl sulfosuccinate, four-arm polyethylene glycol-maleimide and four-arm polyethylene glycol-N-hydroxysuccinimide ester penetrate through the surface of the mulberry bark into the interior. Under weakly alkaline conditions, four-arm polyethylene glycol-maleimide and four-arm polyethylene glycol-N-hydroxysuccinimide ester react, and amines and N-hydroxysuccinimide esters react to form stable amide bonds, forming a uniform cross-linked structure inside the mulberry bark, which plays a filling and reinforcing role.
[0035] S7, post-processing
[0036] The modified mulberry bark is pre-dried, fluffed, combed and dried to obtain mulberry bark cellulose fiber.
[0037] Preferably, the pre-drying is performed using an agitation dryer, the pre-drying temperature is 35-40° C., the time is 1-2 hours, and the agitation rate is 100-200 r / min.
[0038] Preferably, the drying temperature is 50-60° C. and the drying time is 3-4 hours.
[0039] Due to the adoption of the above technical solution, the technical effects achieved by the present invention are:
[0040] 1. The mulberry cellulose fiber prepared by the present invention has a length of 34 to 38 mm, a fineness of 1.33 to 2.22 dtex, good uniformity of a single fiber, and a coefficient of variation of linear density of less than 3%; the surface is smooth and soft to the touch, and the average roughness is 311 to 323 nm.
[0041] 2. The mulberry cellulose fiber prepared by the present invention has excellent mechanical properties, a breaking strength of 12.28-13.74 CN / dtex, an elongation at break of 20.3-22.6%, and a strength unevenness rate of less than 1%.
[0042] 3. The present invention adopts a method combining microwave treatment, biological degumming and chemical degumming, the residual glue rate in the fiber is less than 3.2%, and the degumming effect is better.
[0043] 4. Under the effect of pre-drying, the water inside the mulberry bark evaporates evenly, the cross-linked structure shrinks to a certain extent, and the structure between the cellulose macromolecules becomes more uniform and dense; in addition, there is a hydrogen bond between the cross-linked structure and the cellulose macromolecules in the mulberry bark, the overall strength of the fiber increases, and the strength unevenness rate decreases significantly. The polyethylene glycol macromolecules in the cross-linked structure are flexible structures, so the mulberry bark cellulose fiber has good elasticity, feels softer and more comfortable, and the elongation at break is also significantly improved.
[0044] 5. When the mulberry cellulose fiber prepared by the present invention is blended with cotton fiber, the surface hairiness is significantly reduced, the yarn is softer, and the application range is wider. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with specific embodiments.
[0046] Example 1
[0047] S1. Microwave treatment
[0048] Soak the mulberry bark in water and microwave it, then dry it in the sun for 24 hours after cooling, and then beat it to remove impurities.
[0049] The power of the microwave treatment is 800 W and the time is 25 min.
[0050] S2. Preprocessing
[0051] The mulberry bark obtained by microwave treatment was immersed in an acid bath for 70 minutes and then washed with water.
[0052] The acid bath includes citric acid, wherein the concentration of the citric acid is 2 g / L, the temperature of the acid bath is 55° C., and the bath ratio is 1:19.
[0053] S3. Microbial fermentation treatment
[0054] The mulberry bark obtained by pretreatment is added into the composite bacterial liquid for fermentation treatment, and then washed with water after the treatment.
[0055] The mass fraction of the composite bacterial liquid is 22%; the composite bacterial liquid contains EM bacteria, Bacillus licheniformis and Bacillus subtilis, and the mass ratio of the EM bacteria, Bacillus licheniformis and Bacillus subtilis is 5:11:3; the EM bacteria, Bacillus licheniformis and Bacillus subtilis are all purchased from Shandong Xinzhuoyuan Chemical Co., Ltd.
[0056] The temperature of the fermentation treatment is 32° C. and the fermentation time is 3 days.
[0057] S4. Enzyme degumming treatment
[0058] The mulberry bark treated with microbial fermentation is added into an active enzyme solution for enzymatic degumming treatment.
[0059] The concentration of laccase in the active enzyme solution is 0.5 g / L, and the concentration of pectinase is 1.2 g / L; the temperature of the enzyme degumming treatment is 47° C., the time is 7 hours, and the bath ratio is 1:29.
[0060] The enzyme activity of the laccase is 10000U, and the enzyme activity of the pectinase is 8600U.
[0061] S5, Cooking
[0062] The mulberry bark treated with enzyme degumming is added into alkali solution for scouring, and then washed with water after scouring.
[0063] The concentration of sodium hydroxide in the alkali solution is 14 g / L, the concentration of sodium tripolyphosphate is 6 g / L, and the concentration of sodium silicate is 9 g / L.
[0064] S6. Modification
[0065] The mulberry bark after being washed with water was first added into the permeate and soaked for 50 minutes, with a bath ratio of 1:11; then added into the phosphate buffer solution, heated to 32°C and reacted for 3 hours to obtain the modified mulberry bark.
[0066] The preparation method of the permeate is as follows: four-arm polyethylene glycol-maleimide, four-arm polyethylene glycol-N-hydroxysuccinimide ester, and dioctyl sodium sulfosuccinate are added into deionized water and stirred for 10 minutes to obtain the permeate.
[0067] In terms of weight, the permeate contains 12 parts of four-arm polyethylene glycol-maleimide, 15 parts of four-arm polyethylene glycol-N-hydroxysuccinimide ester, 2 parts of sodium dioctyl sulfosuccinate, and 90 parts of deionized water.
[0068] The pH of the phosphate buffer is 8.
[0069] S7, post-processing
[0070] The modified mulberry bark is pre-dried, fluffed, combed and dried to obtain mulberry bark cellulose fiber.
[0071] The pre-drying was carried out using a stirring dryer, the pre-drying temperature was 38° C., the time was 2 h, and the stirring rate was 150 r / min.
[0072] The drying temperature is 55° C. and the drying time is 3.5 h.
[0073] Example 2
[0074] S1. Microwave treatment
[0075] Soak the mulberry bark in water and microwave it, then dry it in the sun for 24 hours after cooling, and then beat it to remove impurities.
[0076] The power of the microwave treatment is 600 W and the time is 20 min.
[0077] S2. Preprocessing
[0078] The mulberry bark obtained by microwave treatment was immersed in an acid bath for 60 minutes and then washed with water.
[0079] The acid bath includes citric acid, wherein the concentration of the citric acid is 1.5 g / L, the temperature of the acid bath is 50° C., and the bath ratio is 1:18.
[0080] S3. Microbial fermentation treatment
[0081] The mulberry bark obtained by pretreatment is added into the composite bacterial liquid for fermentation treatment, and then washed with water after the treatment.
[0082] The mass fraction of the composite bacterial liquid is 20%; the composite bacterial liquid contains EM bacteria, Bacillus licheniformis and Bacillus subtilis, and the mass ratio of the EM bacteria, Bacillus licheniformis and Bacillus subtilis is 4:10:2; the EM bacteria, Bacillus licheniformis and Bacillus subtilis are all purchased from Shandong Xinzhuoyuan Chemical Co., Ltd.
[0083] The temperature of the fermentation treatment is 30° C. and the fermentation time is 2 days.
[0084] S4. Enzyme degumming treatment
[0085] The mulberry bark treated with microbial fermentation is added into an active enzyme solution for enzymatic degumming treatment.
[0086] The concentration of laccase in the active enzyme solution is 0.4 g / L, and the concentration of pectinase is 1 g / L; the temperature of the enzyme degumming treatment is 45° C., the time is 6 hours, and the bath ratio is 1:28.
[0087] The enzyme activity of the laccase is 10000U, and the enzyme activity of the pectinase is 8600U.
[0088] S5, Cooking
[0089] The mulberry bark treated with enzyme degumming is added into alkali solution for scouring, and then washed with water after scouring.
[0090] The concentration of sodium hydroxide in the alkali solution is 12 g / L, the concentration of sodium tripolyphosphate is 5 g / L, and the concentration of sodium silicate is 7 g / L.
[0091] S6. Modification
[0092] The mulberry bark after being boiled and washed was first added into the permeate and soaked for 40 minutes, with a bath ratio of 1:10; then added into the phosphate buffer solution, heated to 30°C and reacted for 2 hours to obtain the modified mulberry bark.
[0093] The preparation method of the permeate is as follows: four-arm polyethylene glycol-maleimide, four-arm polyethylene glycol-N-hydroxysuccinimide ester, and dioctyl sodium sulfosuccinate are added into deionized water and stirred for 5 minutes to obtain the permeate.
[0094] In terms of weight, the permeate contains 10 parts of four-arm polyethylene glycol-maleimide, 13 parts of four-arm polyethylene glycol-N-hydroxysuccinimide ester, 1 part of sodium dioctyl sulfosuccinate, and 85 parts of deionized water.
[0095] The pH of the phosphate buffer is 7.7.
[0096] S7, post-processing
[0097] The modified mulberry bark is pre-dried, fluffed, combed and dried to obtain mulberry bark cellulose fiber.
[0098] The pre-drying is carried out using a stirring dryer, the pre-drying temperature is 35° C., the time is 1 hour, and the stirring rate is 100 r / min.
[0099] The drying temperature is 50° C. and the drying time is 3 hours.
[0100] Example 3
[0101] S1. Microwave treatment
[0102] Soak the mulberry bark in water and microwave it, then dry it in the sun for 24 hours after cooling, and then beat it to remove impurities.
[0103] The power of the microwave treatment is 1000 W and the time is 30 min.
[0104] S2. Preprocessing
[0105] The mulberry bark obtained by microwave treatment was immersed in an acid bath for 80 minutes and then washed with water.
[0106] The acid bath includes citric acid, wherein the concentration of the citric acid is 3 g / L, the temperature of the acid bath is 60° C., and the bath ratio is 1:20.
[0107] S3. Microbial fermentation treatment
[0108] The mulberry bark obtained by pretreatment is added into the composite bacterial liquid for fermentation treatment, and then washed with water after the treatment.
[0109] The mass fraction of the composite bacterial liquid is 24%; the composite bacterial liquid contains EM bacteria, Bacillus licheniformis and Bacillus subtilis, and the mass ratio of the EM bacteria, Bacillus licheniformis and Bacillus subtilis is 6:12:4; the EM bacteria, Bacillus licheniformis and Bacillus subtilis are all purchased from Shandong Xinzhuoyuan Chemical Co., Ltd.
[0110] The temperature of the fermentation treatment is 35° C. and the fermentation time is 3 days.
[0111] S4. Enzyme degumming treatment
[0112] The mulberry bark treated with microbial fermentation is added into an active enzyme solution for enzymatic degumming treatment.
[0113] The concentration of laccase in the active enzyme solution is 0.6 g / L, and the concentration of pectinase is 1.5 g / L; the temperature of the enzyme degumming treatment is 50° C., the time is 8 hours, and the bath ratio is 1:30.
[0114] The enzyme activity of the laccase is 10000U, and the enzyme activity of the pectinase is 8600U.
[0115] S5, Cooking
[0116] The mulberry bark treated with enzyme degumming is added into alkali solution for scouring, and then washed with water after scouring.
[0117] The concentration of sodium hydroxide in the alkali solution is 16 g / L, the concentration of sodium tripolyphosphate is 8 g / L, and the concentration of sodium silicate is 10 g / L.
[0118] S6. Modification
[0119] The mulberry bark after being boiled and washed was first added into the permeate and soaked for 60 minutes, with a bath ratio of 1:12; then added into the phosphate buffer solution, heated to 35°C and reacted for 4 hours to obtain the modified mulberry bark.
[0120] The preparation method of the permeate is as follows: four-arm polyethylene glycol-maleimide, four-arm polyethylene glycol-N-hydroxysuccinimide ester, and dioctyl sodium sulfosuccinate are added into deionized water and stirred for 8 minutes to obtain the permeate.
[0121] In terms of weight, the permeate contains 14 parts of four-arm polyethylene glycol-maleimide, 16 parts of four-arm polyethylene glycol-N-hydroxysuccinimide ester, 3 parts of sodium dioctyl sulfosuccinate, and 95 parts of deionized water.
[0122] The pH of the phosphate buffer is 8.5.
[0123] S7, post-processing
[0124] The modified mulberry bark is pre-dried, fluffed, combed and dried to obtain mulberry bark cellulose fiber.
[0125] The pre-drying is carried out using a stirring dryer, the pre-drying temperature is 40° C., the time is 1.5 hours, and the stirring rate is 200 r / min.
[0126] The drying temperature is 60° C. and the drying time is 4 hours.
[0127] Comparative Example 1
[0128] Representative Example 1 was selected, and step S6 was removed, while the rest was consistent with Example 1, as Comparative Example 1.
[0129] Comparative Example 2
[0130] Representative Example 1 was selected, and the pre-drying in step S7 was removed, while the rest was consistent with Example 1, as Comparative Example 2.
[0131] The properties of the mulberry cellulose fibers prepared in Examples 1-3 and Comparative Examples 1-2 were tested, as shown in Table 1.
[0132] Table 1
[0133] Test items Average length (mm) Average fineness (dtex) Average roughness (nm) Linear density coefficient of variation (%) Breaking strength (CN / dtex) Elongation at break (%) Strength unevenness rate (%) Example 1 38 1.33 311 2.23 13.74 20.3 0.45 Example 2 35 1.67 323 2.64 12.28 22.6 0.83 Example 3 34 2.22 318 2.47 12.96 21.2 0.67 Comparative Example 1 31 1.11 675 18.3 6.5 11.8 33.9 Comparative Example 2 36 1.56 455 12.51 11.58 17.36 13.2
[0134] As can be seen from Table 1, the mechanical properties, uniformity and smoothness of the fiber in Comparative Example 1 are reduced by removing the modification. This is because the fiber is damaged to a certain extent after the non-cellulose substances are removed from the mulberry bark, so the linear density coefficient of variation and the strength unevenness rate are significantly increased, and the mulberry bark cellulose fiber obtained after the modification is fuller and denser, so the average length and average fineness are slightly increased, the strength and surface properties of the fiber are enhanced, and the overall performance of the fiber is improved. Comparative Example 2 removes the pre-drying, and the evaporation of water inside the mulberry bark is uneven, resulting in a decrease in the overall performance of the fiber relative to Example 1.
[0135] Unless otherwise specified, the ratios and percentages described in the present invention are all weight ratios and weight percentages; and the raw materials are all commercially available.
[0136] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing mulberry cellulose fiber, characterized in that: The preparation method includes microwave treatment, pretreatment, microbial fermentation treatment, enzyme degumming treatment, scouring, modification and post-treatment; The modification is as follows: the mulberry bark after being boiled and washed is first added into the permeate and soaked for 40 to 60 minutes, with the bath ratio being 1:10 to 12; then added into the phosphate buffer, heated to 30 to 35° C. and reacted for 2 to 4 hours to obtain the modified mulberry bark; The preparation method of the permeate is as follows: four-arm polyethylene glycol-maleimide, four-arm polyethylene glycol-N-hydroxysuccinimide ester, and dioctyl sodium sulfosuccinate are added to deionized water and stirred for 5 to 10 minutes to obtain the permeate; In terms of weight, the permeate contains 10 to 14 parts of four-arm polyethylene glycol-maleimide, 13 to 16 parts of four-arm polyethylene glycol-N-hydroxysuccinimide ester, 1 to 3 parts of sodium dioctyl sulfosuccinate, and 85 to 95 parts of deionized water; The pH of the phosphate buffer is 7.7 to 8.5; The post-treatment is to pre-dry, fluff, comb and dry the modified mulberry bark to obtain mulberry bark cellulose fibers; The pre-drying adopts a stirring dryer, the pre-drying temperature is 35-40°C, the time is 1-2h, and the stirring rate is 100-200r / min; The drying temperature is 50-60° C. and the drying time is 3-4 hours.
2. The method for preparing mulberry cellulose fiber according to claim 1, characterized in that: The microwave treatment comprises immersing the mulberry bark in water for microwave treatment, cooling the bark and drying it in the sun for 24 hours, and beating the bark to remove impurities. The power of the microwave treatment is 600-1000W, and the time is 20-30min.
3. The method for preparing mulberry cellulose fiber according to claim 1, characterized in that: The pretreatment is to immerse the mulberry bark obtained by microwave treatment in an acid bath for 60 to 80 minutes and then wash it with water; The acid bath comprises citric acid, wherein the concentration of the citric acid is 1.5-3 g / L; the temperature of the acid bath is 50-60° C., and the bath ratio is 1:18-20.
4. The method for preparing mulberry cellulose fiber according to claim 1, characterized in that: The microbial fermentation treatment comprises adding the mulberry bark obtained by the pretreatment into a composite bacterial solution for fermentation treatment, and then washing with water after the treatment is completed; The mass fraction of the composite bacterial solution is 20-24%; the composite bacterial solution contains EM bacteria, Bacillus licheniformis and Bacillus subtilis, and the mass ratio of the EM bacteria, Bacillus licheniformis and Bacillus subtilis is 4-6:10-12:2-4; The temperature of the fermentation treatment is 30-35° C., and the fermentation time is 2-3 days.
5. The method for preparing mulberry cellulose fiber according to claim 1, characterized in that: The enzymatic degumming treatment is to add the mulberry bark treated by microbial fermentation into an active enzyme solution for enzymatic degumming treatment.
6. The method for preparing mulberry cellulose fiber according to claim 5, characterized in that: The concentration of laccase in the active enzyme solution is 0.4-0.6 g / L, and the concentration of pectinase is 1-1.5 g / L; the temperature of the enzyme degumming treatment is 45-50° C., the time is 6-8 hours, and the bath ratio is 1:28-30; The enzyme activity of the laccase is 10000U, and the enzyme activity of the pectinase is 8600U.
7. The method for preparing mulberry cellulose fiber according to claim 1, characterized in that: The scouring is to add the mulberry bark treated by enzyme degumming into alkali solution for scouring, and then wash it with water after scouring; The concentration of sodium hydroxide in the alkali solution is 12-16 g / L, the concentration of sodium tripolyphosphate is 5-8 g / L, and the concentration of sodium silicate is 7-10 g / L.
8. The mulberry cellulose fiber prepared by the method for preparing mulberry cellulose fiber according to any one of claims 1 to 7, characterized in that: The mulberry cellulose fiber has a length of 34-38 mm, a fineness of 1.33-2.22 dtex, a breaking strength of 12.28-13.74 CN / dtex, a breaking elongation of 20.3-22.6%, and a strength unevenness rate of less than 1%.
Citation Information
Patent Citations
Preparation method of antibacterial fiber adsorption film
CN106311154A
Graphene modified cellulose membrane and preparation method thereof
CN107417937A